A Case of Adult Clival Osteomyelitis. (May 2022) - Kayode-Ajala, Fisayo; Williams, Neil; Ejikeme, Chidinma; Walji, Ali; Farrer, William
Clival osteomyelitis is a potentially life-threatening skull base infection. It is rare and generally challenging to diagnose and treat. Clival osteomyelitis is typically seen in the pediatric population and is very rare in the adult population. It occurs as a complication of recurring paranasal infections and malignant otitis externa. The exact pathophysiology of osteomyelitis of the clivus is relatively uncertain. Here, we describe a case of a 36-year-old man with medical history significant for hypertension and poorly controlled type 1 diabetes mellitus who experienced recurrent paranasal sinus infection for 2 years. He received multiple antibiotic treatments and underwent adenoidectomy without substantial improvement of symptoms. Ultimately, a diagnosis of the clival osteomyelitis through the help of a computed tomography (CT) scan of the paranasal sinus and neck was made. This diagnosis allowed for adequate intervention and treatment of our patient with subsequent resolution of his presenting symptoms. This case highlights the importance of high suspicion for clival osteomyelitis in patients with recurring sinus infections.